Preparation and UCST-type phase behavior of glycopolypeptides in alcoholic solvents. Issue 130 (21st December 2015) - Wang, Xi; Ge, Chenglong; Ling, Ying; Tang, Haoyu
Abstract : Glycopolypeptides with mannose pendants exhibited a reversible UCST-type phase behavior in various alcoholic solvents. The solution phase transition temperature was related to the solvent, concentration, main-chain length, and side-chain composition. Abstract : Glycopolypeptides with different contents of tetra- O -acetyl-d -(+)-mannopyranoside and tetra- O -hydroxyl-d -(+)-mannopyranoside pendants were prepared via copper-mediated [2 + 3] alkyne-azide 1, 3-dipolar cycloaddition. Glycopolypeptides with high contents of tetra- O -acetyl-d -(+)-mannopyranoside ( x ≥ 44%) exhibited a reversible UCST-type phase behavior in both methanol and ethanol. FTIR analysis revealed that the mechanism of the UCST-type phase behavior originated from the hydrophobic interaction and H-bonding between the polymers and the H-bonding between the polymer and solvent. Variable-temperature UV-vis analysis revealed that the UCST-type transition temperatures ( T pt s) of the resulting glycopolypeptides increased as the polymer concentration or main-chain length increased. Incorporation of proton donating groups ( i.e., tetra- O -hydroxyl-d -(+)-mannopyranoside) or increasing the number of carbons of aliphatic alcohols led a decrease of maximal concentration and increase of T pt .